Comprehensive Clinical Trial Data Summation for BRAF‐MEK Inhibition and Checkpoint Immunotherapy in Metastatic Melanoma. (7th May 2019) - Luke, Jason J.
Abstract: Background: Immune checkpoint inhibitors, along with BRAF and MEK inhibitors, have dramatically changed the management of and outlook for patients with metastatic melanoma. Analyses of long‐term follow‐up data and subanalyses based on disease characteristics may inform clinical decision making. Methods: Reports of clinical trials in metastatic melanoma published between January 1, 2012, and August 30, 2018, were identified using PubMed (terms: melanoma AND [dabrafenib OR trametinib OR vemurafenib OR cobimetinib OR encorafenib OR ipilimumab OR nivolumab OR pembrolizumab]) and were systematically reviewed. Relevant congress proceedings were also assessed. Efficacy data from key phase III trials were analyzed and trends identified. Results: Substantial improvements in objective response rates, progression‐free survival, and overall survival were documented across 14 identified publications. Subgroup findings supported that patients with lower disease burden derive greater benefit than patients with more advanced disease, limiting the value of disease burden in the clinical decision‐making process. However, these agents consistently conferred benefits despite the presence of poor prognostic features. Several clinically relevant questions remain, including how best to sequence immune checkpoint inhibitors and combination targeted therapy. Conclusion: This research, coupled with ongoing investigations, including those on predictive biomarkers, suggests that the treatment decision‐making process is likely to become more nuanced. Implications for Practice: The management of melanoma has been rapidly advancing with new classes of agents, including immune checkpoint and BRAF inhibitors. With long‐term follow‐up, their impact on response rates and survival outcomes is well documented. Additional findings from subgroup analyses suggest that patients with lower disease burden derive greater benefit, yet both consistently confer benefit in patients with higher disease burden. Currently, there is a paucity of data to guide first‐line treatment selection between immunotherapy and BRAF‐targeted therapy in clinical practice or to estimate their impact when sequenced. Gaining these insights will facilitate a more nuanced management approach. Abstract : This review focuses on checkpoint and BRAF inhibitors, exploring outcomes based on clinical and disease characteristics to identify trends that might inform treatment decisions for the management of melanoma.